PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2018) - Chika Deva Ciptadi; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This study aims to analyze the effect of Capital Structure as measured by Debt ro Equity Ratio (DER) and Company Size using a measure of Total Assets to Retrun on Assets (ROA). In this study using companies that belong to the Group of Companies in the Basic Industry and Chemistry for the 2016-2018 Period. This study uses a quantitative approach. The population in this study amounted to 59 companies. The research sample used purposive sampling technique. The method of data analysis in this study used the normality test, the classic assumption test. The results show a negatively influential capital structure that is not significant for company performance. This shows that the higher the debt composition in the company's capital structure will reduce the Company's performance. The influence of Company Size has a significant positive effect on Company Performance because the larger the size of the company, can encourage an increase in the portion of funds that the company can use for production activities.Keywords: Capital Structure, Company Size, Company Performance